The Effect of Organizational Innovation Mediates between Knowledge Management Capabilities and Hotel Performance: A Conceptual Analysis - Syed Jamal Abdul Nasir Syed Mohamad; Nor Shahrul Nizam Muhamad Nor; Amily Fikry; Muhammad Ridzuan Abdul Aziz (Information Management and Business Review, 2023)
The mediation relationship of organizational innovation (OI) between knowledge management capabilities (KMC) and hotel performance (HP) in Malaysia is the focus of this study. According to the World Tourism Organization (2018), around 1.245 billion foreign tourists visited the world in 2016, and the business is expected to generate trillions of dollars in revenue. Unfortunately, this industry has been impacted by the COVID-19 pandemic, which began in early 2020 but has since slowly recovered since 2022 (UNWTO, 2022). To survive in the cut-throat climate, hoteliers in the tourism sector must adopt the prevailing fashion. As a result, hoteliers must equip their staff with the necessary knowledge of infrastructure and processes to handle organizational innovation to ensure they can perform and survive. Nonetheless, a large number of them continue to resist knowledge management adaptation as a creative organization. This initial stage of the conceptual paper is the development of knowledge management, organizational innovation and hotel performance. The data were collected from selected hotels among their top management such as chief executive officers, general managers, managing directors or department managers that represent three-star to five-star hotels in Malaysia by using simple random sampling from the list provided by the Ministry of Tourism, Art and Culture of Malaysia. The result can be expected to assist organizations including hoteliers to sustain competitiveness by having knowledge management capabilities and organizational innovation in the market.